Analisis Kepuasan Pengguna Aplikasi DANA Menggunakan Metode TAM dan EUCS - Fitratul Aini; Fitriani Muttakin; Tengku Khairil Ahsyar; Eki Saputra (Jurnal Sistem Cerdas, 2023)
The DANA application is a payment system service that can be used via a smartphone, which can be in the form of fund transfers, electronic wallets, electronic money and other supporting services. User satisfaction with the application is very important, because it can be used as an assessment material for improving the service quality of the application. By combining two methods, namely the Technology Acceptance Model (TAM) which contains the variables Perceived Usefulness, Perceived Ease of Use and Attitude Toward Using and End User Computing Satisfaction (EUCS) which contains the variables Content, Accuracy, Format, Ease of Use and Timeliness to measure application user satisfaction DANA is the aim of this research. The technique that will be used to collect data is by distributing questionnaires to DANA application users. Through lameshow calculations, there were 100 respondents in this study. Based on the results of the analysis carried out, there are 6 hypotheses that are accepted, namely Perceived Usefulness, Content, Accuracy, Format, Ease of Use and Attitude Toward Using and 2 hypotheses are rejected, namely Perceived Ease of Use and Timeliness. The results obtained through SEM analysis are classified as good with an R-Square correlation value of 75.2% for user satisfaction variables.